Analisis Strategi Customer Interaction Melalui Pre-Event Virtual dalam Pemasaran Trade Expo Indonesia 2024 - Kamiil, Muhammad Daffa; Akbar, Djuni (Program Studi MICE, Jurusan Administrasi Niaga, Politeknik Negeri Jakarta, 2025)
This study analyzes the effectiveness of customer interaction strategies implemented during the virtual pre-event seminars of Trade Expo Indonesia (TEI) 2024, with a focus on their contribution to enhancing trust and participation among international buyers. Employing a qualitative case study approach on the official organizer of TEI 2024, this research draws on data collected through participatory observation and documentation analysis of seminars targeting the Japanese, Dutch, and East African markets. The findings highlight that interaction models centered on direct dialogue with official government trade representatives—such as Trade Attachés and the Indonesian Trade Promotion Center (ITPC)—serve as a critical factor. This strategy achieved up to a 90% participation rate, demonstrating that interactive sessions, particularly discussions and Q&A segments, significantly reinforce buyer trust. Implicatively, the study suggests that pre-event virtual strategies emphasizing authoritative interaction may serve as an effective model for international B2B event marketing, functioning as a catalyst to foster engagement and convert audiences into exhibition participants.